Low-dose trofosfamide plus rituximab is an effective and safe treatment for diffuse large B-cell lymphoma of the elderly: a single center experience - Roland Christian Schelker; Wolfgang Herr; Albrecht Reichle; Martin Vogelhuber (BMC Cancer, 2018)
Abstract Background Rituximab plus combination chemotherapy with cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) is broadly accepted as standard for the treatment of diffuse large B-cell lymphoma (DLBCL). Nevertheless, there is sparsely data concerning the management of elderly patients. Methods We performed a retrospective study of treatment with rituximab and low-dose trofosfamide in elderly patients (≥ 75 years) with DLBCL who were not suitable for R-CHOP or R-CHOP-like regimens or who did not consent to aggressive treatment. The choice regarding the qualification for R-CHOP or R-CHOP-like regimen was left to the estimation of the treating physicians. Results Eleven patients with a median age of 83 years (range, 75–90 years) were included. The age-adjusted international prognostic index was low risk in one patient, low-intermediate in four patients, high-intermediate in three patients, and high risk in 3 patients. All patients were evaluable for response. Five patients (45%) achieved a complete response, three (27%) a partial response, one (9%) stable disease, and two (18%) progressive disease. The estimated 1-yr overall survival was 54.5%, and the estimated 1-yr progression-free survival 45.5%, however, three patients (27%) were alive without evidence of disease at 16–20 months from start of treatment. Main toxicity was leukopenia (36% grade III or IV), whereas grade III/IV non-hematological adverse events did not occur. Conclusions Due to its potency and low toxicity, trofosfamide/rituximab might represent an alternative therapy for DLBCL of elderly patients not suitable for R-CHOP. This observation, however, should be confirmed in a larger patient population within a prospective clinical trial.